Ratib Saman: Tradition, Faith, and Law In Pulau Tengah, Kerinci - Adsa, Ranta; Azwar, Zainal (Suhuf: International Journal of Islamic Studies, 2025)
Religious traditions in Indonesia reflect the dynamic interaction between Islamic teachings and local culture, as seen in the Ratib Saman practice in Pulau Tengah Village, Kerinci, Jambi. This study explores how Islamic law engages with Indonesian traditions. Ratib Saman, a collective zikr with distinctive movements inherited from the Samaniyah Sufi order, is deeply rooted in the community’s socio-religious life. Using a descriptive qualitative method, observation, interviews, and literature review, the study finds that Ratib Saman is institutionalised within traditional social structures through the roles of religious and community leaders. Based on the concept of ‘urf, it is categorised as ‘urf ‘amali, ‘urf khās, and ‘urf ṣaḥīḥ, as it is well-known, beneficial, and consistent with Sharia principles. Ratib Saman strengthens social cohesion, nurtures spirituality, and preserves local Islamic heritage. Although some view its expressive zikr movements as bid‘ah, the uṣūl al-fiqh perspective affirms its legitimacy as long as it aligns with core Islamic teachings. Thus, Ratib Saman represents not only a form of worship but also a manifestation of local wisdom that enriches Indonesia’s Islamic tradition.